2021
DOI: 10.3390/medicina57060570
|View full text |Cite
|
Sign up to set email alerts
|

Planning Implementation Success of Syncope Clinical Practice Guidelines in the Emergency Department Using CFIR Framework

Abstract: Background and Objectives: Overuse and inappropriate use of testing and hospital admission are common in syncope evaluation and management. Though guidelines are available to optimize syncope care, research indicates that current clinical guidelines have not significantly impacted resource utilization surrounding emergency department (ED) evaluation of syncope. Matching implementation strategies to barriers and facilitators and tailoring strategies to local context hold significant promise for a successful imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…So, although the package did significantly improve clinician compliance, there remains room to improve how it is delivered and supported to better address barriers that are not yet mitigated (e.g., knowledge and beliefs, culture, learning climate, complexity, lack of champions, etc.). Li and colleagues report a similar experience from a 2021 study that used CFIR‐ERIC to implement a syncope management pathway 50 . They measured both implementation and compliance outcomes and found that, although there was high acceptability at 91.7% (22 of 24 participant responses), the intervention was only performed on 15–40% of patients across providers 50 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, although the package did significantly improve clinician compliance, there remains room to improve how it is delivered and supported to better address barriers that are not yet mitigated (e.g., knowledge and beliefs, culture, learning climate, complexity, lack of champions, etc.). Li and colleagues report a similar experience from a 2021 study that used CFIR‐ERIC to implement a syncope management pathway 50 . They measured both implementation and compliance outcomes and found that, although there was high acceptability at 91.7% (22 of 24 participant responses), the intervention was only performed on 15–40% of patients across providers 50 …”
Section: Discussionmentioning
confidence: 99%
“…Li and colleagues report a similar experience from a 2021 study that used CFIR‐ERIC to implement a syncope management pathway 50 . They measured both implementation and compliance outcomes and found that, although there was high acceptability at 91.7% (22 of 24 participant responses), the intervention was only performed on 15–40% of patients across providers 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFIR-ERIC Implementation Strategy Matching Tool (CFIR, 2021) offers a structured approach to identifying strategies to implementation barriers and has been recently used in a variety of settings to conceptualize provider views and refine implementation processes (Godbee et al, 2019;Juckett et al, 2020;Li et al, 2021;Waltz et al, 2019). Given that HCHV Employment Specialists overlap with homeless and employment providers both within VHA and the broader community, the CFIR offered an appropriate tool to understand these separate spheres and their impact on implementation efforts.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The outputs of this tool include implementation strategies in relation to the input on CFIR determinants, along with percentages, which reflect the proportion of experts that have endorsed the strategy as being appropriate to address each CFIR determinant [ 21 ]. It has been previously used in empirical studies to guide the identification of implementation strategies [ 24 26 ], ( www.cfirguide.org/choosing-strategies ). This study aims to use our previous studies [ 15 , 27 ] to identify relevant implementation strategies for identified implementation determinants, contextualise the strategies for our setting and obtain expert consensus on the most relevant strategies for implementing pet robots in care homes and nursing homes for PLWD.…”
Section: Introductionmentioning
confidence: 99%